Mejora de la lectura en 2º de Primaria mediante un programa de tutoría entre iguales - Ripoll-Salceda, Juan Cruz; Bravo-Iriso, Celia; Irurzun-Peruchena, Mikel; Pérez-Pérez, Encarna; Zuazu-Martínez, Ana Begoña (ISL (Investigaciones sobre lectura, 2016)
Peer tutoring has proven to be an effective method for teaching reading. In this experiment 106 2nd grade students received nine sessions of the LEO-PAR-D peer tutoring program. Participants performed reciprocal tutoring, supervising partner reading, asking questions and giving points for reading or responding correctly. In addition, they made predictions and answared to questions about the texts. The reading level was assessed before and after intervention with the tests ACL-2, TECLE and PEES. In all three cases there was a significant improvement. The effect size was small for reading comprehension and moderate for reading efficiency. The results of this experiment indicate that the LEO-PAR-D program could be useful in improving some aspects of reading, therefore, further investigation is warranted to evaluate the program effectiveness with a stronger design.
Keywords: Lectura - Comprensión; Comprehension; Cooperative learning; Peer teaching; Reading